2012
DOI: 10.1111/j.1745-6584.2012.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Wadi Aquifers by Artificial Recharge with Treated Waste Water

Abstract: Fresh water resources within the Kingdom of Saudi Arabia are a rare and precious commodity that must be managed within a context of integrated water management. Wadi aquifers contain a high percentage of the naturally occurring fresh groundwater in the Kingdom. This resource is currently overused and has become depleted or contaminated at many locations. One resource that could be used to restore or enhance the fresh water resources within wadi aquifers is treated municipal waste water (reclaimed water). Each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 74 publications
(104 reference statements)
0
40
0
Order By: Relevance
“…These dams are often used as potential sources for drinking water. The southern part has the valley basins, which often dry up due to higher evaporation, excessive use of water and low precipitation [26][27][28]. Past studies reported an approximately 50% increase in evaporation between 2011 and 2050 [2].…”
Section: Implications On Water Resources and Qualitymentioning
confidence: 99%
“…These dams are often used as potential sources for drinking water. The southern part has the valley basins, which often dry up due to higher evaporation, excessive use of water and low precipitation [26][27][28]. Past studies reported an approximately 50% increase in evaporation between 2011 and 2050 [2].…”
Section: Implications On Water Resources and Qualitymentioning
confidence: 99%
“…Notes: 1 The assumed total dynamic head is estimated to be 122 m; 2 Real cost of electric power in the KSA is estimated to range from $0.05-0.15/kw-h.…”
Section: Conveyance Costmentioning
confidence: 99%
“…For centuries, these agrarian communities relied upon shallow groundwater resources to supply potable and irrigation water demands [1]. Anthropogenic impacts, including over-pumping and contamination, have combined to deplete or render unusable the groundwater in shallow alluvial aquifers underlying the wadis [1][2][3]. Because of the low population density, generally small contribution of crop production to the national economy, and the arid nature of the climate, there are quite limited options available to supply the necessary water to maintain these populations.…”
Section: Introductionmentioning
confidence: 99%
“…When rainfall does occur, it is an intense event that causes flash floods through ephemeral channels, known as wadis [2,3]. Flood water passing through the wadi channels allows some recharge to the underlying alluvial aquifer, but most of the water is lost to discharge to tidal water or evaporates with only 3% to 10% being captured as recharge [4][5][6]. Recent research on future climatic changes in this region suggests that a greater degree of variability will occur with longer drought periods and more intense rainfall events with corresponding floods [7,8].…”
Section: Introductionmentioning
confidence: 99%